Training transfer for sustainable agricultural intensification in Tanzania: critical considerations for scaling - up - Sseguya, H.; Bekunda, Mateete A.; Muthoni, F.; Flavain, F.; Masigo, J. (2018)
Sustainable Intensification (SI) in agriculture is fronted as a promising approach to increase agricultural production in Sub-Saharan Africa countries. Technologies that can lead to realization of the SI goal are available but one of the key challenges is the low reach among smallholder farmers due to, among others, ineffective training and co-learning. In this study, a survey methodology was used to obtain data from 145 trainees in a sustainable intensification intervention in Kongwa and Mvomero districts, Tanzania, to analyze the drivers of training transfer. Hierarchical linear regression revealed that motivation of trainees, training design and delivery, and work environment (peer, extension and local institutional support) had positive effects on transfer of the training. For successful transfer of training, recommendations given were a deliberate focus on selection of suitable trainees and ensuring their motivation to learn; use of appropriate documentation, extension and training methods; strengthening farmers’ networks for peer learning; and strengthening collaborations with local institutions.